Large scale synthesis of Si3N4@SiOx core-shell structure nanowires by direct nitridation. Issue 10 (July 2020) - Lan, Yu; Li, Xiaomin; Luo, Jinpeng; Huang, Yi; Pan, Zongming; Wei, Xiuqin; Zhou, Lang; Yin, Chuanqiang
Abstract: In this work, millimeter-scale Si3 N4 @SiOx core-shell structure nanowires were synthesized using the direct nitridation method without the use of catalysts. The silicon powders used as raw materials were pretreated at 1300 °C for 3 h under ammonia. The ammonia was then converted into a nitrogen/hydrogen gas mixture and heated at 1350 °C for another 5 h. The morphology and structure of the as-obtained nanowires were investigated in detail. The Si3 N4 @SiOx nanowires with a core-shell structure were composed of a crystalline α-Si3 N4 core and an amorphous SiOx shell. The formation of the α-Si3 N4 core nanowire is due to the reaction of the N2 gas with the byproduct SiO gas. However, the formation of the amorphous SiOx shell is related to the deposition location of the samples. For the inner part of the samples, the SiOx shell derives from the deposition of the byproduct SiO gas at 1350 °C, while the SiOx shell of the external part of the samples likely derives from the oxidation of the silicon nitride core during the cooling process.